Post‐hematopoietic stem cell transplant hemophagocytic lymphohistiocytosis or an impostor: Case report and review of literature. (25th March 2018) - Vatsayan, Anant; Pateva, Irina; Cabral, Linda; Dalal, Jignesh; Abu‐Arja, Rolla
Abstract: HLH occurring after HSCT is a relatively rare disease. Many conditions may mimic or trigger HLH in post‐HSCT period (eg, cytokine release syndrome, engraftment syndrome, graft rejection/failure, acute graft‐vs‐host disease, infections systemic inflammatory response syndrome/sepsis, and thrombotic microangiopathy). Moreover, this period is usually marked by febrile illness, cytopenia, and a "cytokine storm" leading to elevation of inflammatory biomarkers like ferritin and sCD25. These parameters overlap with the diagnostic criteria for HLH. Such confounding factors make the management of post‐HSCT HLH quite challenging. We illustrate this critical issue with case report of a patient who was diagnosed with HLH after allogeneic HSCT for tAML. He received MP and CsA for HLH but VP‐16 was not administered due to fear of severe myelosuppression. Fortunately, he responded well to treatment and remains in remission to date. We recommend caution while using HLH‐94/HLH‐2004 guidelines for the diagnosis and management of post‐HSCT HLH. In this article, we pinpoint these issues with a brief review of all the pediatric cases and clinical studies of post‐HSCT HLH along with a critical evaluation of its various diagnostic criteria. Finally, based on the limitations of current diagnostic criteria, we suggest a need for formulating disease‐specific diagnostic criteria for post‐HSCT HLH.